Modulation of multidrug resistance by three bisbenzyl-isoquinolines in comparison with verapamil - Tian Hui; Pan Oi-Chao (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To compare cycleanine (Cyc), insularine (Insr), insulanoline (Insn) and verapamil (Ver) in modulation of multidrug resistance (MDR) in vitro. METHODS: The cytotoxic effect was determined by 3-[4, 5-dimethylthiazol-2-yl], 5-diphenyl tetarzolium bromide (MTT) assay. The intracellular doxorubincin (Dox) accumulation was assayed by spectrofluorometer. RESULTS: Cyc, Insr, Insn, and Ver showed significant activities in modulating Dox and vincristine resistances in acquired resistant MCF-7/Adr and KBv200 cell lines in a dose-dependent manner. Cyc, Insr, Insn, and Ver increased intracellular Dox accumulation in MCF-7/Adr cells. Cyc and Insr had greater activities than Ver in modulating MDR, while Insn had similar activity to that of Ver. CONCLUSION: MDR was modulated by Cyc, Insr, and Insn, due to the increase of intracellular Dox accumulation.